Water, ice, society, and ecosystems in the Hindu Kush Himalaya: an introduction - Wester, P.; Chaudhary, S.; Maharjan, A.; Steiner, J. F.; Chettri, N.; Chettri, R.; Jackson, M.; Nepal, Santosh; Wang, X. (International Centre for Integrated Mountain Development, 2023)
This chapter provides an introduction to the Water, ice, society, and ecosystems in the HKH (HI-WISE) assessment report. It provides an overview of the assessment scope and covers key concepts and frameworks used across the report.